THE CONNECTION BETWEEN THE COLORS MENTIONED IN THE HOLY QURAN AND ITS SIGNIFICANCE THE GREEN MODEL - Mohammad Mahmoud al-Domi (European Scientific Journal, ESJ, 2015)
The Holy Quran mentioned the colors and its differences and urged people to think about the pattern and diversity of colors that appear among them. Such and include the different colors of their skin. But let focus our discussion about the color green. The green color is better who comes with predominant color of life. Likely the color of nature, plant, trees and fruit are signs that the earth are living. Green color also represent the color of paradise and its named after its signifier like the dark green tree of the paradise. The people of heaven also wearing dress in the green color, their beds and furniture also comes in likely which the color that the prophet peace be upon him loved.